PENGGUNAAN DAN PEMAANFAATAN CYBERSPACE DALAM GERAKAN PEMIKIRAN HIZBUT TAHRIR - Ambar Sri Lestari; Shabrur Rijal Hamka (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This research aims to analyze the use and utilization of cyberspace as new media (internet) in the movement thought of Hizbut Tahrir at IAIN Kendari. The findings of the situation show that the use and utilization of cyberspace via the internet with the Facebook as one of the social media by either students who follow the activities of the intra or extra campus or who does not enter the organization by taking samples in the first half of the even and odd semester students of 2016/2017nwhich consists of eight classes indicate that they  are more panic when it comes to the use of Facebook taking up to 0.89 or 89%. From the use of this social media, then the process of movement of thought against religious doctrine can be done through cyberspace started from the ndividual level, the level of interaction between the individual and community level; cybersociety (virtual community) and finally form a culture (Cyberculture) by a movement of Hizbut  Tahrir. The process of religious doctrine is done through several methods, namely: participation, openness, communication, community, dependency/connectedness.